Understanding environmental models in their legal and regulatory context - Fisher, E; Pascual, P; Wagner, W (2010)
Environmental models are playing an increasingly important role in most jurisdictions and giving rise to disputes. Despite this fact, lawyers and policy-makers have overlooked models and not engaged critically with them. This is a problematic state of affairs. Modelling is a semi-autonomous, interdisciplinary activity concerned with developing representations of systems and is used to evaluate regulatory behaviour to ensure it is legitimate. Models are thus relevant to lawyers and policy-makers but need to be engaged with critically due to technical, institutional, interdisciplinary and evaluative complexities in their operation. Lawyers and policy-makers must thus think more carefully about models and in doing so reflect on the nature of their own disciplines and fields. © The Author [2010]. Published by Oxford University Press. All rights reserved. For Permissions, please email: journals.permissions@oxfordjournals.org.